Transition of Care for Children with High-Grade Central Nervous System Tumors - Ellenbogen, Yosef; Yang, Kaiyun; Ajani, Olufemi (Journal of Pediatric Neurology, 2020)
The increase in survival rates of children with high-grade central nervous system tumors has highlighted the necessity for and challenges associated with transition of care as these children grow into adult life. Late recurrence and treatment effects are some of the conditions that require care after transition. Several models of transition have been proposed in the literature. An effective transition will not only ensure adequate continuity of care but will also include assessment of effectiveness of the transition by health care personnel and the patient/patient's family themselves.
Keywords: transition; pediatric; tumors